Utilization of Empty Oil Palm Bunch as an Alternative of Organic Fertilizer at PTPN III Labuhanbatu Selatan - Yuli Atfrikahani Harahap; Khairunnisa Hasibuan; Wirdah Sufazein Dalimunthe; Abdurrozzaq Hasibuan (Formosa Journal of Science and Technology, 2023)
The development of the area of ​​oil palm plantations in Indonesia is increasing every year. So many empty palm fruit bunches produced from palm oil mills. Oil Palm Empty Bunches (EFB) is a type of solid waste that is mainly produced by palm oil mills. Empty palm kernels, e.g. Materials with a high water content are only processed in the palm oil industry due to the high cost and inefficiency of transporting and disposing of them. The purpose of this article is to discuss the use of empty fruit or palm fronds as an alternative to organic fertilizer at PTPN III Labulasel from previous research. In writing this article, the research article literature search method was used in the Google Scholar database. The criteria for the selected articles are articles published in national magazines in 2018-2023. Library research was carried out by comparing research methods, processing and results of each article. Based on the results of a literature search, it is known that empty bunches or fronds of PTPN III Labusel's oil palm can be used as an alternative organic fertilizer that can be used as plant fertilizer, especially for the oil palm plant itself, and this avoids the accumulation of dirt.